TREATMENT OF DIPYLIDIUM CANINUM INFECTION IN A LOCAL DOG ALONG WITH SUPPORTIVE THERAPY USING LIVRON-B PLEX® AND FISH OIL - Pasek, I Made Abhiwedam; Arjentinia, I Putu Gde Yudhi; Soma, I Gede (Buletin Veteriner Udayana, 2026)
Dipylidium caninum is a tapeworm that inhabits the small intestine of dogs and cats, particularly in warm and humid regions. It has an indirect life cycle that requires fleas as intermediate hosts and vertebrates as definitive hosts. This parasite is considered zoonotic because it can be transmitted to humans through ingestion of infected fleas or dog ticks. Dogs are common companion animals that require proper care and management, both for their health and for the well-being of the humans who keep them. The case animal in this report is a female dog named Aci, 4 months old, weighing 4.2 kg, with orchid-brown hair. This study was conducted to identify D. caninum infection in this dog. Based on the anamnesis, physical examination, clinical assessment, and supporting diagnostic tests, the dog was diagnosed with D. caninum infection, with a favorable prognosis. Causal therapy was administered using a deworming medication (Caniverm®), at a dose of ½ tablet containing fenbendazole, pyrantel embonate, and praziquantel. Supportive therapy included vitamin B-complex (Livron B.plex tablets), and fish oil was provided to promote hair growth. Evaluation of the dog’s condition five days after therapy indicated significant improvement, as evidenced by fecal examination showing no presence of worms. Routine deworming is recommended every three months. Infected animals should be quarantined to prevent transmission to other pets, bathed regularly, and kept in a clean environment. Feces in the yard should be promptly removed to reduce the risk of reinfection.